2009
DOI: 10.1016/j.ijdevneu.2009.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Repeated restraint stress and corticosterone injections during late pregnancy alter GAP‐43 expression in the hippocampus and prefrontal cortex of rat pups

Abstract: In the offspring of prenatal stress animals, overactivity and impaired negative feedback regulation of the hypothalamic-pituitary-adrenal axis are consistent finding. However, little was known about how prenatal stress can permanently alter developmental trajectories of pup's brain. Growth-associated protein-43 (GAP-43) is a presynaptic membrane phosphoprotein whose expression increases during developmental events such as axonal outgrowth or remodeling and synaptogenesis. Phosphorylation of GAP-43 by protein k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 79 publications
4
16
0
Order By: Relevance
“…This demonstrated that GAP-43 expression was sensitive to prenatal stress. Change of GAP-43 expression by prenatal stress was also observed in other studies (Jutapakdeegul et al, 2010;Neeley et al, 2011). GAP-43 has been termed a "growth" or "plasticity" protein and is considered a crucial component of the axon and presynaptic terminal (Strittmatter et al, 1995;Benowitz and Routtenberg, 1997).…”
Section: Discussionsupporting
confidence: 63%
“…This demonstrated that GAP-43 expression was sensitive to prenatal stress. Change of GAP-43 expression by prenatal stress was also observed in other studies (Jutapakdeegul et al, 2010;Neeley et al, 2011). GAP-43 has been termed a "growth" or "plasticity" protein and is considered a crucial component of the axon and presynaptic terminal (Strittmatter et al, 1995;Benowitz and Routtenberg, 1997).…”
Section: Discussionsupporting
confidence: 63%
“…Prenatal stress, such as may be associated with severe famine situations, can lead to permanent changes in HPA axis function, including exacerbated synaptic pruning in regions associated with the HPA axis [225] as well as changes in GR and MR [181,226] and altered glucocorticoid responses to stress [182,227,228]. This altered sensitivity of the HPA axis could potentially lead to changes in glucocorticoid-mediated appetite regulation and energy storage.…”
Section: Glucocorticoidsmentioning
confidence: 99%
“…Prenatal stress can interfere with synaptic pruning during brain development in regions that are important for HPA axis control, the prefrontal cortex (Spencer et al 2005) and hippocampus (Jacobson and Sapolsky 1991). In particular, it has recently been determined that growth-associated protein of 43 kDa (GAP-43), an intracellular protein involved in the establishment and reorganization of synaptic connections during development (Pfenninger et al 1991;Larsson 2006), is up-regulated in the second week after birth and reduced in adulthood in offspring from restraint-stressed dams (Jutapakdeegul et al 2010). These findings indicate that prenatal stress can produce lasting changes in the connectivity of these regions, potentially affecting HPA axis sensitivity in the long term.…”
Section: Mechanisms For Perinatal Stress Effects On Body Weight Regulmentioning
confidence: 99%